CULTIVATION OF GURBAK MELON IN KARAKALPAKSTAN USING HYDROGEL - Xudaynazarova, Mohigul Ilhomovna; Saparniyazov, In’omjan Artiqbaevich (SCIENCE and SOCIETY, 2026)
The article presents information on the rational use of water resources in agrocenoses in Karakalpakstan and the growth and development of the Gurvak melon variety when grown using hydrogel in a water-scarce environment, and the effect of hydrogel on biometric indicators.
Keywords: water scarcity; melon; hydrogel; resource-saving; productivity